80.5k views
0 votes
Simplify (5^x+2-5^x)/5^x×4

Simplify (5^x+2-5^x)/5^x×4-example-1
User Ken Brown
by
4.8k points

1 Answer

2 votes

Answer:

6

Explanation:

The given expression is,


(5^(x+2)-5^x )/(5^x*4)

Now, we know that,


a^(m+n) = a^m . a^n

Then,


5^(x+2)=5^x . 5^2

So,


(5^(x+2)-5^x)/(5^x*4)=(5^x.5^2-5^x)/(5^x*4)

Now, taking
5^(x) common from the numerator of the given expression, then


(5^(x+2)-5^x)/(5^x*4)=(5^x(5^2-1))/(5^x*4)


\implies(5^(x+2)-5^x )/(5^x*4)=(5^2-1)/(4)


\implies(5^(x+2)-5^x)/(5^x*4)=(5*5-1)/(4)=(25-1)/(4)


\implies(5^(x+2)-5^x)/(5^x*4)=(24)/(4)=6

So, the simplified form of the given expression gives the result 6.

User Stephenfrank
by
4.6k points